Mother Tongue Education: A Quest of Quality and Access in Education - Khadka, Bishnu Kumar (Journal of NELTA Surkhet, 2018)
As it is claimed and is the ground reality that language is not everything but everything is nothing in education without language. Moreover, language shapes the learning and learning begins with language. In this regards, this article attempts to review the multilingual perspectives in terms of access and quality in education through mother tongue based education advocacy. It is theoretical in nature which is based on the secondary sources of theoretical review and tries to justify with policy and practice based rational for mother tongue education in Nepalese context. Journal of NELTA Surkhet, Vol. 5 January, 2018, Page: 65-74